Association of Sjögren's Syndrome With Reduced Lifetime Sex Hormone Exposure: A Case–Control Study. Issue 9 (31st August 2020) - McCoy, Sara S.; Sampene, Emmanuel; Baer, Alan N.
Abstract : Objective: To test whether cumulative estrogen exposure, as determined by age at menarche, age at menopause, female hormone use, hysterectomy, and parity, have an effect on the development of primary Sjögren's syndrome (SS). Methods: We performed a case – control study of 2, 680 women from the Sjögren's International Collaborative Clinical Alliance registry, including 1, 320 registrants with primary SS and 1, 360 with sicca symptoms but no key features of primary SS (sicca controls). The composite estrogen score (CES) was calculated by point assignment for early menarche (age ≤10 years), high parity (>3 pregnancies), hysterectomy, female hormone use, and late menopause (age ≥53 years). Cumulative menstrual cycling (CMC) was calculated as years menstruating minus time pregnant. Results: Using a regression model that adjusted for age, recruitment site, ethnicity, education, employment status, and smoking, we observed a progressive inverse trend between primary SS and CES. The odds ratio (OR) and 95% confidence interval (95% CI) were as follows for the sicca control group: CES 1, OR 0.81 (95% CI 0.67–0.99); CES 2, OR 0.74 (95% CI 0.57–0.97); CES 3, OR 0.50 (95% CI 0.30–0.86). This trend was corroborated by analysis of CMC. At the highest level of CMC within the postmenopausal group there was a 24% reduction in cumulative sex hormone exposure among primary SS participants relative to controls. Conclusion: Women with primary SS have lower estrogen exposure and CMC compared to sicca controls. Increasing estrogen exposure was negatively associated with development of primary SS. Further longitudinal studies of sex hormone exposure in primary SS are needed to confirm these findings.